EUROPEAN CITIZENS AND HEALTH SPORTS (Fiep Bulletin - online, 2014)
Everybody knows nowadays that regular practice of physical activities, even at a moderate intensity, have beneficial effects on the improvement of health. A number of recent studies confirm that a sedentary way of living and lack of exercise constitute main factors of risk for our health. In a document composed of different chapters, the author describes the origins and the development of "sport for all" or "health-sport" in Europe, with Germany as an example of positive development of mass-sport. Afterwards he explains the structures of the European bodies intervening in this field, with precisions given by Yves Le Lostecque about the competencies of the European Commission in the field of sport. Follows an analysis of the structures and the different forms of physical and sports activities for younger people, for adults and for seniors, including a view on the main organisers of those activities. A special chapter treats the education for health-sport in the schools and a short view on the vista of health-sport concludes this document.